Impacts of Protease Sources on Growth and Carcass Response, Gut Health, Nutrient Digestibility, and Cecal Microbiota Profiles in Broilers Fed Poultry-by-Product-Meal-Based Diets - Muhammad Shahbaz Zafar; Shafqat Nawaz Qaisrani; Saima; Zafar Hayat; Kashif Nauman (Metabolites, 2025)
Background: The current study aimed to evaluate the effects of the supplementation of protease sources on growth and carcass response, gut health, nutrient digestibility, and cecal microbiota profiles in broilers fed poultry-by-product-meal (PBM)-containing diets. Methods: In total, 800 one-day-old mixed-sex broilers (Arbor Acres) were weighed and allocated to one of the four dietary treatments in a completely randomized design, with eight replicates and 25 birds each per replicate. The treatments were as follows: (1) T0, control diet (without protease supplementation and 3% PBM); (2) T1, control diet supplemented with acidic protease at 100 g/ton (50,000 U/g); (3) T2, control diet supplemented with alkaline protease at 200 g/ton (25,000 U/g); (4) T3, control diet supplemented with neutral protease at 200 g/ton (25,000 U/g). Results: Protease supplementation enhanced (p < 0.05) body weight gain and the feed conversion ratio, predominantly in broilers fed PBM-based diets containing alkaline protease. Alkaline protease supplementation increased (p < 0.05) the apparent ileal digestibility of proteins (AIDP) by 4.3% and the apparent ileal digestibility of amino acids (AIDAA) by up to 5.8%, except for ornithine. Increments (p < 0.05) in carcass, breast, and leg quarter yields due to protease supplementation were evident, particularly in broilers fed diets containing alkaline protease. Alkaline protease improved (p < 0.05) the duodenal villus height (VH), reduced the crypt depth (CD), and increased the villus height to crypt depth ratio (VCR). Alkaline protease supplementation reduced (p < 0.05) cecal counts of Salmonella, Escherichia coli, and Clostridium in the broilers, whereas it increased (p < 0.05) the Lactobacillus counts. Conclusions: the supplemented alkaline protease resulted in improved growth performance and carcass traits, better gut health, as well as improved ileal digestibility of nutrients, including crude protein (CP) and acid insoluble ash (AIA), with a more balanced cecal microbial composition in broilers.